STUDI TENTANG FAKTOR-FAKTOR PENYEBAB KESULITAN BELAJAR MENYIMAK BAHASA INGGRIS PADA MAHASISWA SEMESTER III PBI IAIN RADEN INTAN LAMPUNG TAHUN PELAJARAN 2015/2016 - Kurniawati, Dewi (Universitas Islam Negeri Raden Intan Lampung, 2015)
Learning English is very complex because the English language consists of four skills namely listening, speaking, writing and reading. But in fact, many students still can not understand the word or phrase spoken in English. So many factors that students feel when they have difficulties in learning English listening. The difficulty arises from two factors: internal and external factors, therefore the author intends to examine where the difficulties in terms of internal factors and external factors.This research is descriptive qualitative as studies on issues generate descriptive data, or in other words, in this study the collection of data contained in the form of reports and descriptions. Its population was the students of English Program Study 3rd semester of Tarbiyah and Teacher Treaning Faculty the State of Islamic Studies Raden Intan Lampung in the academic year of 2015/2016. The sample of this research were 40 people consisting of 33 women and 7 men.From the result of this research found that the factors causing difficulty in listening to students are; declining health condition or illness, the elusive material, a lack of support, lack of training to improve English listening whether with their classmates or with native speaker.